Distributions of Cranial Pathologies Provide Evidence for Head-Butting in Dome-Headed Dinosaurs (Pachycephalosauridae) - Peterson, Joseph E. (Public Library of Science, 2013)
Pachycephalosaurids are small, herbivorous dinosaurs with domed skulls formed by massive thickening of the cranial roof. The function of the dome has been a focus of debate: the dome has variously been interpreted as the product of sexual selection, as an adaptation for species recognition, or as a weapon employed in intraspecific combat, where it was used in butting matches as in extant ungulates. This last hypothesis is supported by the recent identification of cranial pathologies in pachycephalosaurids, which appear to represent infections resulting from trauma. However, the frequency and distribution of pathologies have not been studied in a systematic fashion. Here, we show that pachycephalosaurids are characterized by a remarkably high incidence of cranial injury, where 22% of specimens have lesions on the dome. Frequency of injury shows no significant difference between different genera, but flat-headed morphs (here interpreted as juveniles or females) lack lesions. Mapping of injuries onto a digitial pachycephalosaurid skull shows that although lesions are distributed across the dome, they cluster near the apex, which is consistent with the hypothesis that the dome functioned for intraspecific butting matches.